REPRODUCTIVE ATTITUDES OF THE STUDENT YOUTH (a review of empirical studies) - Nazarova, I.B.; Zelenskaya, M.P. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2017)
The article summarizes the results of the studies of reproductive attitudes of the Russian students (born in 1982-2000) published in 2000-2017. Students lack life experience, thus, they make moral choices under conflicting media information and sometimes even propaganda of certain values or anti-values concerning family, marriage, and motherhood (paternity). A low level of students’ awareness of the main issues in planning and creating a family, giving birth to children, taking care of their health is accompanied by an early start of active and risky sexual life. Despite the unconditional authority and positive example of parents, most young people independently search for information about sexual relations and sometimes get negative and painful experience. There are three types of young people: (1) the majority respect traditional family values, try (or wish) to follow them and to some extent succeed; (2) a significant part respect traditional family values but cannot or do not want to follow them (including approving and practicing cohabitation); (3) about a tenth do not respect and do not follow traditional values concerning marriage and family, refuse and oppose them; marriage does not matter for such students, they have no desire to give birth and raise a child, do not think about the morality of relationships between sexes, po-lygamy, abandonment of the child or abortion. Students indicate factors influencing their family plans and reproductive behavior: social-psychological (own beliefs, opinion of the closest people, limitation of the time resource; unplanned pregnancy and perception of abortion; availability and quality of the partner; social-psychological maturity; perceptions of the future - confidence in it); religiosity; experience (example of the parents’ family); social-demographic (age; structure of the parents’ family); economic (availability and quality of housing; financial situation); physical (health status); institutional (state family policy, influence of the church and media, values and traditions of society). Thus, the young people reproductive attitudes and the idea of a family are determined by various factors including values and traditions of the closest social circle and society in general.